2011
DOI: 10.1080/13607863.2011.562177
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese version of the Geriatric Anxiety Inventory: Transcultural adaptation and psychometric validation

Abstract: These findings provide initial evidence that the Portuguese version of the GAI is a valid and reliable measure for assessing late-life anxiety and highlights the need for possible modifications of the instrument before being used in other languages and cultural groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 24 publications
2
41
0
2
Order By: Relevance
“…Scores higher than 8-9 points correspond to the presence of symptoms of potential severe anxiety. The Portuguese version of the scale has high internal consistency (Cronbach's alpha ¼ .96), with ICC values of 0.995 for test-retest and good concurrent validity with the State Anxiety Inventory (r ¼ .631, p < .001); the Geriatric Depression Scale (r ¼ .860, p < .001); and the General Health Questionnaire (r ¼ .763, p < .001) (Ribeiro, Paúl, Simões, & Firmino, 2011).…”
Section: Geriatric Anxiety Inventorymentioning
confidence: 99%
“…Scores higher than 8-9 points correspond to the presence of symptoms of potential severe anxiety. The Portuguese version of the scale has high internal consistency (Cronbach's alpha ¼ .96), with ICC values of 0.995 for test-retest and good concurrent validity with the State Anxiety Inventory (r ¼ .631, p < .001); the Geriatric Depression Scale (r ¼ .860, p < .001); and the General Health Questionnaire (r ¼ .763, p < .001) (Ribeiro, Paúl, Simões, & Firmino, 2011).…”
Section: Geriatric Anxiety Inventorymentioning
confidence: 99%
“…Authors from the Portuguese version found a cut-off point for severe anxiety symptoms at levels of 8-9 (Ribeiro et al, 2011). Participants are asked to agree or disagree with the 20 sentences describing how they felt during the last week.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The Geriatric Anxiety Inventory (GAI) (Pachana et al, 2007), validated for the Portuguese population (Ribeiro, Paúl, Simões, & Firmino, 2011) was used for assessing anxiety symptoms. Authors from the Portuguese version found a cut-off point for severe anxiety symptoms at levels of 8-9 (Ribeiro et al, 2011).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…To detect cognitive deficits we used two brief screening instruments, namely MMSE (Morgado et al, 2009), the widely used brief screening instrument, and MoCA (Freitas et al, 2011), developed to screen milder forms of cognitive impairment through the assessment of six cognitive domains. To assess depressive and anxious symptoms in older adults we used Geriatric Depression Scale contained 30 items (Barreto et al, 2008) and Geriatric Anxiety Inventory (Ribeiro et al, 2011), respectively. The presence of subjective memory complains was assess by SMC (Ginó et al, 2008), and finally, the M@T-PT was used.…”
Section: Materials and Proceduresmentioning
confidence: 99%